Professional DNN7 : open source .NET CMS platform - Walker, Shaun, 1971- (Wrox professional guides., 2015)
This book provides thorough coverage of all aspects of DNN including the latest features, APIs and updates. DNN site builders, administrators, and developers will learn how to: determine if they have met the installation requirements and install DNN; administer and host a DNN site and install and configure modules; manage users and keep a DNN installation secure; localize a DNN site for multiple languages; build custom DNN modules in C# using the model of separation of database, business logic, and presentation layers; customize the DNN look with skinning; make their site social with EVOQ. Other topics include: information about venture capital funding, commercialization, and software business insights. --